Commercial immunoassays in paraneoplastic neurological syndromes: an Australian laboratory perspective - Ali, Syed B.; Cecchin, Amelia; Burfoot, Rebecca; Chia, Nicholas; Ravindran, Janakan; Field, Deborah; King, Jovanka; Pucar, Phillippa A.; Banovic, Tatjana (Frontiers in Neurology, 2025)
BackgroundParaneoplastic antibodies are implicated in heterogeneous clinical presentations. Commercial immunoassays include indirect immunofluorescence (IIF), and line immunoblot (LIB). LIB can be associated with false positives, and unfortunately, further confirmatory assays are not readily available in diagnostic laboratories.ObjectivesTo determine frequency of positive LIB on serum or cerebrospinal fluid (CSF) using EUROLine paraneoplastic neurological syndromes (PNS) 12 Ag Test kit (EuroImmun, Germany) and establish concordance with IIF on Nova Lite kit (Inova Diagnostics, United States) and clinical presentation.MethodsA retrospective analysis of all LIB performed over a four-year period was undertaken. Healthy control samples were also analysed with IIF and LIB.ResultsTwo thousand and eighty-one LIB samples were processed, 91 (4.4%) were positive from 69 patients with a median age of 64 years. There were 37 females (53.6%). Some samples had two antibody specificities (n = 6, 6.6%). Of those with one antibody, GAD65 (n = 22), Yo (n = 19), SOX1 (n = 17) and amphiphysin (n = 14) were most frequent. Of the positive LIBs, 80 (87.9%) had concurrent IIF and eight samples (10%) had a typical IIF pattern. Clinical relevance of a positive LIB, irrespective of IIF, was seen in 15/91 samples (14.3%) from nine patients; GAD65 (n = 3), Hu (n = 2), amphiphysin (n = 1), Yo (n = 1), Tr (n = 1) and CV2 (n = 1). Of the 71 healthy controls, five (7.0%) had a positive LIB: medium band (n = 4, 5.6%: amphiphysin, CV2, SOX1 and Yo) and strong band (n = 1, 1.4%: Yo). All IIF were negative. On average, signal intensity (SI) was higher in those with disease (SI 77.3/very strong band) compared to those without (SI 28.6/strong band) and healthy controls (SI 2/negative band) (p < 0.0001).DiscussionLIB has a high false positive rate, and in this cohort, there were more false than true positive results. The assay must be used in those with a high clinical suspicion for PNS. While the commercial IIF kit is a useful test, it is insufficient to be used as a screening strategy in isolation.